P78 Recovery priorities for patients with degenerative cervical myelopathy. Issue 3 (14th February 2019) - Davies, Benjamin M; Mowforth, Oliver D; Sadler, Iwan; Aarabi, Bizhan; Kwon, Brian K; Kurpad, Shekar N; Harrop, James; Wilson, Jefferson R; Grossman, Robert; Fehlings, Michael G; Kotter, Mark RN
Abstract : Objectives: The misalignment of patient and researcher objectives has been shown to contribute to research inefficiency and wastage. The patient research priorities in degenerative cervical myelopathy [DCM] are unknown. The present study aimed to establish relevant functional domains and their recovery priority to DCM sufferers. Design: Functional domains were established from qualitative patient interviews (n=4), and the recovery priority through an e-survey (n=659). Subjects: DCM Patients recruited via a DCM charity [Myelopathy.org] and Google Adwords. Methods: Seven functional domains were identified: arm and hand, walking, upper body/trunk, sexual, elimination of pain, normal sensation and bladder/bowel function. Patients were asked to rank these domains. The influence of disease characteristics on selection was analysed. Results: 481 complete responses were analysed. Overall, pain was the most popular recovery priority (39.9%), followed by walking (20.2%), sensation (11.9) and arm and hand function (11.5%). Sexual function (5.7%), bladder and bowel (3.7%) or trunk function (3.5%) were chosen less frequently. With respect to disease characteristics, overall pain remained the recovery priority [with the exception of patients with greater walking impairment (p<0.005) who prioritised walking] even amongst patients with lower pain scores. Conclusions: Pain is a recovery priority for DCM patients, even amongst those reporting low levels of pain.